Performance of Colposcopy Clinic at Comilla Medical College Hospital in 2023 - Begum, Sartaj; Sharmin, Sanzida; Akter, Mst Jesmin (Journal of Comilla Medical College Teachers' Association, 2025)
Background: Cervical cancer was the fourth most common cancer diagnosed globally in 2020, and it was the fourth largest cause of death for women. Various screening procedures are available in Bangladesh, of which VIA is the most popular. VIA +ve cases are being referred to the colposcopy clinic, where evaluation and management is carried out. Objective: To provide an overview of the evaluation and management of VIA +ve cases of colposcopy clinics in Comilla Medical College Hospital. Methods: The study presents a retrospective analysis of records of the colposcopy clinic of Comilla Medical College Hospital (CoMCH) from January 2023 to December 2023. Patients besides Comilla Medical College Hospital, referred from different Upazila health complex, MCWC (Maternal and child welfare center) and, from other districts underwent direct colposcopic evaluation and management. The patient received different types of management such as thermal ablation, loop electrosurgical excision procedure (LEEP), and, biopsy for histopathological examination and they were kept for further follow-up. Result: In this study, a total of 3025 women underwent screening by VIA but among them, 115 (3.8%) women tested positive and referred to the colposcopy clinic in Comilla Medical College Hospital. In addition to these VIA positive women, a total of 1190 women were attending the colposcopy clinic who were referred from different UPZHC for colposcopic evaluation and management. Most of the patients about-70.92% were in the age group between 30-45 years and 74.53% patients were educated up to secondary level. Regarding colposcopic diagnosis 62.7% were normal, 25.21% were CIN I, 2.68% were CIN II, 0.84% were CIN III, and 4.03% were carcinoma cervix. Regarding management, about 4% of the patients were treated by LEEP, 12% patients by thermocuagulation, and biopsy for histopathology were taken from 47% of the patients. Conclusion: In developing countries like Bangladesh, adequate coverage of the total female population by cervical cytology is not possible at present. Colposcopy based “see and treat” protocol is well accepted for management of CIN in Bangladesh. It can reduce the number of visits to the clinic or failure to receive treatment and overall, can reduce the incidence of cervical carcinoma. J Com Med Col Teachers’ Asso Jan 2025; 29(1): 37-40